PENGARUH WAKTU PERKECAMBAHAN TERHADAP TOTAL FENOL, KAROTEN DAN AKTIVITAS ANTIOKSIDAN TEPUNG KECAMBAH JAGUNG (Zea mays L.) - Triana Ardi, Ni Nyoman; Wisaniyasa, Ni Wayan; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p06, 2020)
Zea mays L. is the scientific name for corn which is containing antioxidants such as carotene. Germination of corn can improve nutrition from food due to enzyme activity. This study aims to determine the effect of germination time on total phenol, carotene and antioxidant activity in corn sprouts flour. In this study, the research design used is Completely Randomized Design with five of germination time such as 24, 30, 36, 42 and 48 hours with each treatment was repeated three times. The corn sprouts obtained were then tested for total phenol, carotene and antioxidant activity. The result showed that germination time had a significant effect on total phenol, carotene and antioxidant activity (IC50 and ?-carotene bleaching). The best germination time obtained is 48 hours that had a total phenol level of 11.35 mg/100g, a total carotene level of 1.38 mg/100g, an antioxidant activity (IC50) of 1.32 mg/ml and an antioxidant activity (?-carotene bleaching) of 0.53 mg/ml.